Analysis of Vladimir Putin’s Rationality in The Policy of The Invasion of Ukraine in 2019-2022 - Annisa Diva (Mediasi: Journal of International Relations, 2022)
The study aims to analyze the rationality of Vladimir Putin in the policy of the invasionof Ukraine in 2019-2022. As president of Russia, Putin invaded Ukraine to strengthen thesecurity of his country and protect Russian citizens living on the territory of Ukraine. However,this action has attracted controversy in the eyes of the international community because it isconsidered to violate international law and undermine the stability of the European region. Thisresearch uses a descriptive research method that focuses on analyzing secondary data fromvarious sources such as journal articles, mass media, and government policies. The resultsshowed that Putin used structural and calculative rationality to invade Ukraine. Putin decidedthis because it benefitted his country in the long run. Putin believes that by taking this action,he can strengthen the position of Russia as the main power in the European region, increasepublic support within the country, and gain access to the territory of Ukraine, which is rich innatural resources. However, the invasion by Putin drew condemnation from many countries andinternational organizations. In addition, this action also has a detrimental impact on Ukraineand Russian citizens living in the region. Therefore, this study suggests taking importantpolicies like this to consider the long-term impacts and not just focus on the benefits for thecountry itself